One word from Sophia - Averbeck, Jim (Atheneum Books for Young Readers, an imprint of Simon & Schuster, 2015)
All Sophie wants for her birthday is a pet giraffe, but as she tries to convince different members of her rather complicated family to support her cause, each tells her she is using too many words until she finally hits on the perfect one. Includes glossary.